Knowledge and Perception Regarding the Development and Acceptability of Male Contraceptives Among Pharmacists: A Mixed Sequential Method - Muna Barakat; Samar Thiab; Sara Thiab; Raja’a A. Al-Qudah; Amal Akour (American Journal of Men's Health, 2022)
Community pharmacists play a crucial role in providing comprehensive patient education regarding contraception methods. This study aims to investigate Jordanian pharmacists’ knowledge and perceptions toward male oral contraceptive pills (OCPs). A mixed-explanatory sequential method was divided into two phases. The first was a self-administered electronic survey that was distributed to community pharmacists/trainees in Jordan. The second phase was carried out through online semi-structured in-depth interviews targeting the maximum variation purposive sample of community pharmacists. A total of 158 (response rate 98%) questionnaires were included in the analysis. The majority of the participants were female ( n = 118, 74.2%). In terms of knowledge, only 25% of participants acknowledged the presence of male OCPs and almost half were uncertain about the mechanism of action and the possible uses. The findings of the interviews confirmed a relatively negative perception toward male OCPs and the identified barriers to male OCPs were cultural norms, side effects, and poor compliance. It is argued that there is a negative perception toward male OCPs due to the majority of pharmacists not believing such products will be successful in Jordan. Once these pills are approved for their effectiveness and safety, men may need further education and encouragement to take an active role in family planning along with their partners.